ANALISIS TINGKAT KECEMASAN MATEMATIS SISWA SMA - Hakim, Rosalia Noor; Adirakasiwi, Alpha Galih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to give an idea of how the level of mathematical anxiety of high school students. This type of research is descriptive research with qualitative approach. Measurements of student anxiety are seen during the math learning process. The population in this study was 13 high school X graders. The data collection technique uses a mathematical anxiety scale questionnaire containing 23 statements with 3 indicators and analyzed in descriptive statistical form which is then categorized by 4 categories, including high, medium, low, and very low. After the mathematical anxiety level picture was produced, 4 students were selected where each student represented each category to be analyzed in a positive manner the questionnaire answers that had been given. The results showed that no students experienced excessive anxiety levels or in the category of very high anxiety levels, in the very low category it was seen that the number of students who had less mathematical anxiety levels compared to other anxiety level categories was only 1 student, in the category of low mathematical anxiety levels as many as 3 students, 4 students belonged to the category of high anxiety levels or excessive anxiety levels , while the number of students who experience the most levels of anxiety is included in the category of moderate anxiety levels as many as 5 students.